Gender equity in emergency medicine: Five years on, where are we headed?. (6th December 2021) - Govindasamy, Laksmi Sakura; Terziovski, Milé; Wheeler, Melissa; Rixon, Andrew; Wilson, Samuel
Abstract: The challenge of addressing gender inequality was highlighted in the 2016 Trainee Focus of Emergency Medicine Australasia . Despite increasing numbers of female medical graduates, including increasing female trainees in emergency medicine (EM), this has not yet translated to equal representation in formal leadership roles. Five years later, as the Australasian College for Emergency Medicine (ACEM) welcomes the second female college president, this article explores the gendered leadership gap in EM from an organisational and intersectional feminist perspective and recommends high‐level strategies for change. Notably, ACEM has demonstrated committed engagement with gender equity, such as the establishment of the Advancing Women in Emergency Section. It has also achieved gender parity in provisional trainees and improved women's representation on the ACEM Board. However, broader organisational processes that ensure work–life integration, transparent leadership development pathways and equitable recruitment, promotion, retention and evaluation remain critical. Creating a local evidence‐base to support diversity in leadership development remains a priority.